A quarter century of management research in South Asia – III: analysis and conclusions. (4th September 2020) - Menon, Sanjay T.
Abstract : Purpose: In Part I and Part II of this review series, management research over a 25-year period from 1990 to 2014 from Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan and Sri Lanka was reviewed (Menon, 2016, 2019). This final paper presents further analysis, including author affiliation analysis, and an exploration of contextual factors affecting management research in each of the eight South Asian countries. Design/methodology/approach: Publication trends and the locational affiliation of the authors (in-country vs external) were analyzed. Country-specific analysis and policy recommendations were developed from an ecological and institutional theory perspective. Findings: There were a total of 1, 250 management research articles related to South Asian countries published in 183 journals, with the most being in the International Journal of Human Resource Management ( n  = 92). The average number of publications per year has steadily increased, nearly doubling in the last five years. An analysis of author affiliations revealed that a majority (64%) of the first authors were based in the West. Originality/value: The author affiliation analysis in this paper is an original technique and offers empirical evidence that much of quality management research on South Asia is undertaken by scholars external to the region. The review series is the first such comprehensive effort covering management research in all eight South Asian countries over a 25-year period and offers country-specific explanations for the state of management research in these countries.